Survey and Five Years Study to Identify the Occurrence and Medical Outline of Numerous Stages of Cancers in Lahore - Asma Mehfooz, Ahmad Javed, Gul Khan, Nazia Shuaib, Shuman Roy, Muhammad Khalil (Pakistan Journal of Medical & Health Sciences, 2022)
Tumor occurrence information collected for various organs were processed through clean up, mixing, conversion, diminution and removal for final illustration. Risk of tumor perceived to be ceaselessly increasing among each males and females. Overall, lymphomas and carcinoma are the foremost common tumor in males and females, severally, in Lahore with virtually the very best rates within the Asian Pacific region. The occurrence of head and neck, brain, and respiratory organ Tumor, in addition as tumor has chop-chop hyperbolic among males, whereas, ovarian, cervix, head and neck and lymphomas became additional common among females. the current Transmission ought to be useful for sufficient planned designing, classification of risk factors and taking acceptable hindrance and management measures at the national level. This analysis was conducted to come up with trends and patterns of commonest male and feminine Tumor from 2012-2017 for the town population of Lahore Pakistan.